Insight into the cryoprotective effect of egg yolk peptides on frozen egg yolk: functional, structural and physicochemical properties - Jiajia Zhang; Yuchang Jin; Yaru Meng; Yaotong Liu; Xiaoxue Yang; Ying Cao; Yanqiu Ma; Xin Gao; Peng Yu (Food Science of Animal Products)
Egg yolk peptides were prepared by enzymatic hydrolysis of defatted egg yolk powder. The cryoprotective effects of these peptides were assessed by examining the functional, structural and physicochemical properties of egg yolk. Results indicated that egg yolk peptides could reduce viscosity and prevent the accumulation of egg yolk proteins during freezing, thereby mitigating the deterioration of its functional characteristics. The peptide hydrolyzed for 3 h demonstrated the lowest fluidity in thawed egg yolk. Additionally, Fourier transform infrared (FTIR) spectra and intrinsic fluorescence spectra revealed that egg yolk peptides could reduce damage to the secondary and tertiary structures of proteins, enhancing the stability of the protein network. Changes in the content of secondary structures showed that egg yolk peptides increased β-turns, decreased β-sheets, and maintained overall structural stability and strength. This study provides new insights for egg yolk peptides to inhibit frozen egg yolk gelation.